1993
DOI: 10.1002/eji.1830230102
|View full text |Cite
|
Sign up to set email alerts
|

Development of human Th1 and Th2 cytokine responses: The cytokine production profile of T cells is dictated by the primary in vitro stimulus

Abstract: Regulation of interleukin (IL)-4 production, but not IL-2 production, was found to be quite different in either freshly isolated T cells or T cell clones. Both fresh T cells and T helper 2-like clones produced IL-4 when stimulated with anti-CD2 in combination with anti-CD28. However, whereas T cell clones showed enhanced IL-4 production when phorbol 12-myristate 13-acetate (PMA) was used in addition to anti-CD2 and anti-CD28, IL-4 production by fresh T cells was inhibited by the presence of PMA. Prestimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…The lymphokine pattern induced by PAF may be influenced by the nature of the antigen, or the cytokine milieu in the local environment [42][43][44]. Taken together, our findings indicate that PAF-induced inflammatory reactions may play a role in both chronic and acute inflammation.…”
Section: Induction Of Il-4 By Pafmentioning
confidence: 76%
“…The lymphokine pattern induced by PAF may be influenced by the nature of the antigen, or the cytokine milieu in the local environment [42][43][44]. Taken together, our findings indicate that PAF-induced inflammatory reactions may play a role in both chronic and acute inflammation.…”
Section: Induction Of Il-4 By Pafmentioning
confidence: 76%
“…Apart from the functional relevance of restricted cytokine patterns a number of groups have investigated what factors may be responsible for the development of the individual T cell subsets [11,15,24,26]. It has been demonstrated that the development of a Thl cytokine profile is associated with the presence of IFN-7, IFN-a and IL-12 and the absence of IL-4 at the time of the priming of the T cells.…”
Section: Discussionmentioning
confidence: 98%
“…After 1 week, irradiated PBMC were added again as feeders; cells were maintained in culture with rIL-2 for additional 2 weeks. Production of IFN-+ and IL-4 by Th clones was analyzed after 24-h stimulation with PMA (10 ng/ml) and anti-CD3 mAb (100 ng/ml) in cell-free supernatants by RIA [39,40].…”
Section: Lymphocyte Separation and In Vitro Stimulation Assaysmentioning
confidence: 99%